Cultural studies:A critical introduction - During,Simon (Routledge, 2017)
Cultural Studies: A Critical Introduction is a wide-ranging and stimulating introduction to the history and theory of Cultural Studies from Leavisism, through the era of the Centre for Contemporary Cultural Studies, to the global nature of contemporary Cultural Studies. Cultural Studies: A Critical Introduction begins with an introduction to the field and its theoretical history and then presents a series of short essays on key areas of Cultural Studies, designed to provoke discussion and raise questions. Each thematic section examines and explains a key topic within Cultural Studies. Sections include: * the discipline * time * space * media and the public sphere * identity * sexuality and gender * value